Designing A Virtual Jakarta Tourism Application On Android Os And Virtual Reality Tools - Arman Syah Putra; Dona; Pas Mahyu Akhirianto; Nurul Aisyah (International Journal of Science, Technology & Management, 2021)
The background of this research is to make a prototype of a Jakarta virtual tourism application system using Android OS and using virtual reality tools. The method used by this panel is to use a literature review and create an application prototype that will be applied to the making of a virtual Jakarta tourism program. The results of this study are the application of virtual reality tools on the Jakarta virtual tourism application which aims to help the tourism sector affected by the COVID-19 pandemic and the manufacture of application prototypes that use the Android OS. The limitation of this research lies in making an application prototype using the Android OS which is not perfect and has not produced a real application. This research is very useful for the development of the tourism sector during the COVID-19 pandemic and in the future, so that tourists can choose to travel online or offline.